Who remained happy despite the pandemic?: the impact of changed life situations and mobility and perceptions and attitudes toward the altered lifestyle during COVID-19 - Yunmi Park; Tae-Hyoung Tommy Gim (Journal of Asian Architecture and Building Engineering, 2025)
This study explored the determinants of happiness during the COVID-19 pandemic by emphasizing a broad range of factors, including individual (i.e. socio-demographic status, life situations, attitudinal and perceptual characteristics) and policy restrictions. In particular, the study delved into the impact of changes in life situations and mobility, as well as perceptions and attitudes toward the altered lifestyle during COVID-19, on happiness. By analyzing data with 75 items from a U.S. nationwide survey in 2020, this study found that socio-demographic factors played a significant role in increasing happiness specifically when income increased and individuals transitioned from unemployment to employment or sustained employment during the pandemic. Happiness was also significantly reduced by COVID-19 altered attitudinal and perceptual changes such as restricted social interactions and activities, perception of infection risk, avoidance of online alternatives, perceived infection risk from close relationships, and a preference for compactness. Individuals who were users of public transportation before COVID-19 reported lower levels of happiness during the pandemic. This comprehensive exploration underscores the multifaceted nature of happiness during the COVID-19 pandemic, highlighting the intertwined roles of socio-demographic factors, changes in life circumstances, and attitudes and perceptions to new life style.